Republic of North Macedonia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of North Macedonia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
The economy is rebounding. After a 6 percent drop in 2020, real GDP is projected to grow at 4 percent both in 2021 and 2022, reflecting improved mobility, a return of the diaspora, and continued policy support. With uncertainty remaining high, including about the course of the pandemic, policies need to be kept flexible. Emphasis should be on limiting the economic scars from the pandemic crisis while making progress on long-standing reform priorities such as further strengthening public financial management and revenue administration and buttressing the financial safety net.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Central African Republic